Influence of iron on growth and absorption of P, K, Ca and Mg by rice plant in nutrient solution - Fageria, Nano Kumar; Barbosa Filho, Morel Pereira; Carvalho, José Ruy Porto de (Pesquisa Agropecuaria Brasileira, 2014)
Rice plants (Oryza sativa L. - cultivar IAC 435) were grown in nutrient solution to evaluate the effect of varying iron concentration on growth and uptake of P, K, Ca, Mg and Fe. Lowest concentration of Fe for optimum growth was 2.5 ppm. Iron toxicity occurred at 80 ppm. Critical toxic level of Fe in the tops of 20 and 40 days old plants were 680 and 850 ppm, respectively. With increasing concentrations of Fe, the content of Fe (ppm) in the tops increased, but total uptake increased up to 60 ppm only, and then decreased. Uptake of P, K, Ca and Mg decreased with increasing concentration of iron in nutrient solution.